Prospek Otonomi Daerah Tingkat Ii Di Indonesia Suatu Kajian Dari Aspek Keuangan (Studi Kasus DATI II Propinsi Jawa Tengah) - Nanga, mUANA (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2002)
Financial ability constitutes one of variables that is crucial by nature to a region (Dati II : regency or municipality) in its effort to realize regional auto numbering into reality. Based on the result of financial condition analysis of region in central java. It can be said that regions in central java on the whole have batter opportunity to achieve regional autonomy being tangible, dynamic, compatible, and responsible accountable. This regard is caused by financial condition of regions in central java which overall better and higher than the average of financial ability of regions nationally.